2013
DOI: 10.1186/1471-2164-14-400
|View full text |Cite
|
Sign up to set email alerts
|

The acute transcriptional response of the coral Acropora millepora to immune challenge: expression of GiMAP/IAN genes links the innate immune responses of corals with those of mammals and plants

Abstract: BackgroundAs a step towards understanding coral immunity we present the first whole transcriptome analysis of the acute responses of Acropora millepora to challenge with the bacterial cell wall derivative MDP and the viral mimic poly I:C, defined immunogens provoking distinct but well characterised responses in higher animals.ResultsThese experiments reveal similarities with the responses both of arthropods and mammals, as well as coral-specific effects. The most surprising finding was that MDP specifically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 62 publications
6
61
0
1
Order By: Relevance
“…GIMAP4 has been earlier localized to the water soluble 25 and microsomal 6 fractions of the cytoplasm, ER and Golgi 1 . GIMAPs are related to septin GTPases known to interact with microtubules and membranes 18 .…”
Section: Resultsmentioning
confidence: 99%
“…GIMAP4 has been earlier localized to the water soluble 25 and microsomal 6 fractions of the cytoplasm, ER and Golgi 1 . GIMAPs are related to septin GTPases known to interact with microtubules and membranes 18 .…”
Section: Resultsmentioning
confidence: 99%
“…GiMAP is also called IAN (immune associated nucleotide binding protein). GiMAPs are ancient in origin, and have been lost in some animal lineages yet undergone expansions in others (Weiss et al, 2013). GiAMPs have been found to play an important role in plant defense and in regulating T-cell development and in maintaining T-cell homeostasis for normal immune function in mammals (Nitta and Takahama, 2007; Reuber and Ausubel, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…GiAMPs have been found to play an important role in plant defense and in regulating T-cell development and in maintaining T-cell homeostasis for normal immune function in mammals (Nitta and Takahama, 2007; Reuber and Ausubel, 1996). Recently, it has been demonstrated that GiMAPs appeared as the most prominent immune factors in the coral Acropora millepora , a basal metazoan, after challenge with the bacterial cell wall-derived muramyl dipeptide and polyinosinic:polycytidylic acid (Weiss et al, 2013). Still, except for mammals, a clear immune role for GiMAPs in the metazoa has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the mechanisms of immune response in corals are just beginning to be studied systematically (Palmer and Traylor-Knowles 2012). Genome and transcriptome analyses from various coral species, including the staghorn corals Acropora digitifera (Shinzato et al 2011), Acropora millepora (Miller et al 2007;Weiss et al 2013), and Acropora cervicornis (Libro et al 2013), the cauliflower coral Pocillopora damicornis (Vidal-Dupiol et al 2013), and the mountainous star coral Orbicella faveolata (previously Montastraea faveolata) (Schwarz et al 2008), have revealed the presence of a variety of conserved immune-type genes predicted to participate in the three functional compartments of any immune reaction, i.e., immune recognition, intracellular signaling, and effector response.…”
Section: Introductionmentioning
confidence: 99%